Teaching reading as a receptive skill - Huszti Ilona; Густі Ілона (Kárpátaljai Magyar Tanárképző Főiskola, 2000)
Abstract. Modern language teachers often find that they must also serve as reading skills teachers since emphasis on reading has become one of the primary curricular concerns in second and foreign language programs. In fact, reading is often the chief goal of learners in countries where English is taught as a foreign language.(Dubin and Bycina, 1991:195) The aims of our paper are to define reading itself, give models of the process of reading and classify the reading errors made by learners of English as a foreign language.
https://opac3.brff.monguz.hu:443/hu/record/-/record/79589
Keywords: Teaching; reading; receptive skill